(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Urinary tract infections (UTIs) caused by Escherichia coli remain a significant therapeutic challenge due to the increasing prevalence of antibiotic-resistant and biofilm-forming strains. Nanotechnology-based drug delivery systems offer a promising strategy to improve the solubility, dissolution, bioavailability, and antibacterial efficacy of conventional antibiotics. In this study, trimethoprim-loaded zinc oxide nanoparticles (TZnONPs) were prepared by the solvent evaporation method and evaluated for their physicochemical properties and antibacterial activity. Zinc oxide nanoparticles were characterized using Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and X-ray diffraction (XRD). TZnONPs prepared with different drug-to-zinc oxide ratios were assessed for particle size, polydispersity index, zeta potential, drug content, entrapment efficiency, and in vitro drug release. The optimized formulation, TZnONPs-1, exhibited a mean particle size of 418.61 ± 7.66 nm, drug content of 93.67 ± 1.05 mg, and entrapment efficiency of 96.49 ± 0.81%. FTIR and differential scanning calorimetry studies confirmed the absence of significant drug–excipient interactions, while XRD indicated the partial amorphous state of trimethoprim within the nanoparticle matrix. SEM analysis revealed spherical and uniformly dispersed nanoparticles. In vitro release studies showed sustained release of 93.49 ± 0.81% within 3 h compared with 29.48 ± 0.81% from the pure drug. Antibacterial testing against E. coli (ATCC 25922) demonstrated that TZnONPs-1 produced a larger inhibition zone (>3.3 cm) than ciprofloxacin (2.2 cm), indicating enhanced antibacterial activity. These results suggest that TZnONPs-1 may serve as a promising nanocarrier for the treatment of drug-resistant and biofilm-associated UTIs caused by E. coli.